"Suffering Twice": The Gender Politics of Cesarean Sections in Taiwan. (13th June 2014) - Kuan, Chen‐I
<x xml:space="preserve">Abstract</x> Women's pursuit of medical interventions in childbirth has been a challenging issue in feminist and medical anthropological research on the medicalization of reproduction. This article addresses the gender politics surrounding maternal requests for cesarean sections in Taiwan. Since the 1990s, Taiwanese cesarean rates have been reported as among the highest in the world. That is not the case now, yet they are still perceived as such, and the current rate of 37% is indeed high by any standards. The government and public discourses attribute the high cesarean rate to women's demand for this intervention. However, my ethnographic research indicates that the Taiwanese hospital birthing system leads to the prevalence of cesareans, and that women's requests for them constitute strategic responses to the system and its existing high cesarean rates. Using women's attempt to avoid "suffering twice" as an example, I argue that maternal requests for cesareans often lie at the intersection between their restricted control over childbirth and their agency within the medical system.